1995
DOI: 10.1007/bf00402171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the hypoglycaemic drugs repaglinide and glibenclamide on ATP-sensitive potassium-channels and cytosolic calcium levels in ? TC3 cells and rat pancreatic beta cells

Abstract: The present study demonstrates the action of the hypoglycaemic drugs repaglinide and glibenclamide in cultured newborn rat islet cells and mouse beta TC3 cells. In cell-attached membrane patches of newborn rat islet cells repaglinide (10 nmol/l) and glibenclamide (20 nmol/l) decrease the open probability of single ATP-sensitive K(+)-channels to approximately 10% of the activity prior to addition of the drugs in short-term experiments (< 5 min). The influence of repaglinide and glibenclamide on the ATP-sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 23 publications
5
66
0
1
Order By: Relevance
“…These estimates agree well with the values reported by Gromada et al [39] on the inhibition of the native channel in rat pancreatic beta cells in culture (IC 50 =0.089 and 0.047 nmol/l, respectively). The upper limit for repaglinide is, however, much lower than the value determined in metabolically poisoned Xenopus oocytes [24].…”
Section: Potency and Efficacysupporting
confidence: 92%
“…These estimates agree well with the values reported by Gromada et al [39] on the inhibition of the native channel in rat pancreatic beta cells in culture (IC 50 =0.089 and 0.047 nmol/l, respectively). The upper limit for repaglinide is, however, much lower than the value determined in metabolically poisoned Xenopus oocytes [24].…”
Section: Potency and Efficacysupporting
confidence: 92%
“…Applying digital Ca 2ϩ imaging on single ␤-TC3 cells, it has been shown that repaglinide and GLY induce a concentration-dependent increase in intracellular free Ca 2ϩ concentration (40 channels because it is inhibited by verapamil. Based on studies of the heart and other tissues, it has been suggested that increases in cytosolic Ca 2ϩ concentration may lead to an increase in intramitochondrial free Ca 2ϩ and activation of several matrix dehydrogenases and increased turnover of the Krebs cycle (41).…”
Section: Fig 5 Effect Of High Glucose (A)mentioning
confidence: 99%
“…The phosphorylation reaction was started by adding 80 -120 nM PKG-I␣ for 15 min at 37°C and stopped by adding Laemmli buffer (3ϫ) containing 10% ␤-mercaptoethanol (36). The phosphorylated proteins were separated on SDS-PAGE, stained, destained, dried, and exposed to Kodak X-Omat film at Ϫ70°C.…”
mentioning
confidence: 99%